VALIDITY AND TEACHERS' RESPONSES TO THE IN ACTION LEARNING DESIGN GUIDEBOOK - Nurmala R; Usman Mulbar; Muhhammad Darwis; Murtafiah (Mathematics Education and Application Journal (META), 2025)
This study aims to develop and validate the In Action learning design guidebook for mathematics in junior high school, as well as test teachers' responses to the guidebook. The research method refers to the Plomp development model, which includes the Preliminary Research Phase, Prototyping Phase, and Assessment Phase. The instruments used were design book assessment sheets, expert response questionnaires, and teacher response questionnaires. The results of the study based on expert validation analysis at the Assessment Phase stage showed that all indicators in the guidebook were in the valid and very valid categories (average assessment ranged from 3.17 to 3.63), indicating the feasibility of the product for implementation. Teacher response trials showed "very positive" results on small group tests (majority of aspects above 75%) and increased on field group tests (most aspects above 86%). However, there are inputs for design simplification, more in-depth explanations, and continuous assistance for usage optimization. Overall, this guidebook meets the eligibility criteria and can be implemented with several improvements based on the teacher's input to improve practicality and readability.  Keywords: Learning design, In Action, Mathematical connections, Mathematics, Teacher response.   Penelitian ini bertujuan untuk mengembangkan dan memvalidasi guidebook  desain pembelajaran In Action untuk matematika di SMP, serta menguji respon guru terhadap guidebook  tersebut. Metode penelitian mengacu pada model pengembangan Plomp, yang meliputi tahapan Preliminary Research, Prototyping Phase, dan Assessment Phase. Instrumen yang digunakan adalah lembar penilaian buku desain, angket respon ahli, dan angket respon guru. Hasil penelitian berdasrkan analisis validasi ahli pada tahap Assessment Phase menunjukkan bahwa semua indikator pada guidebook  berada dalam kategori valid dan sangat valid (rata-rata penilaian berkisar antara 3.17 hingga 3.63), menunjukkan kelayakan produk untuk diimplementasikan. Uji coba respon guru menunjukkan hasil yang "sangat positif" pada uji kelompok kecil (mayoritas aspek di atas 75%) dan meningkat pada uji kelompok lapangan (sebagian besar aspek di atas 86%), mengindikasikan keunggulan, kesesuaian kebutuhan, serta kemudahan penggunaan dan implementasi guidebook . Meskipun demikian, terdapat masukan untuk penyederhanaan desain, penjelasan lebih mendalam, serta pendampingan berkelanjutan untuk optimalisasi penggunaan. Secara keseluruhan, guidebook  ini memenuhi kriteria kelayakan dan dapat diimplementasikan dengan beberapa penyempurnaan berdasarkan masukan guru untuk meningkatkan kepraktisan dan keterbacaan.  Kata Kunci: Desain pembelajaran, In Action, Koneksi matematis, Matematika, Respon guru